2018
DOI: 10.1016/j.jiph.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of and preference for oral rapid HIV testing in The Bahamas

Abstract: Initiatives to increase access to quality rapid HIV diagnostics have had relative success in the Caribbean in recent years, including use of oral rapid HIV testing. However, to date, there has not been any investigation into the performance or acceptability of oral fluids HIV testing in the region. In this cross-sectional study in The Bahamas, 252 persons of unknown serostatus were tested side-by-side with two oral rapid test brands, and the results were compared with the national fingerprick algorithm. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The OraQuick ADVANCE ® Test has proven performance and patient acceptability that is facilitated by specimen flexibility ( Wesolowski et al, 2006 , Pant Pai et al, 2007 , 2012 ; Zachary et al, 2012 , Reynolds & Muwonga, 2014 , Nkenfou et al, 2014 ; Martin et al, 2017 ). The OraQuick ADVANCE ® Test is a simple, three-step protocol providing results in 20 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…The OraQuick ADVANCE ® Test has proven performance and patient acceptability that is facilitated by specimen flexibility ( Wesolowski et al, 2006 , Pant Pai et al, 2007 , 2012 ; Zachary et al, 2012 , Reynolds & Muwonga, 2014 , Nkenfou et al, 2014 ; Martin et al, 2017 ). The OraQuick ADVANCE ® Test is a simple, three-step protocol providing results in 20 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, facility-based HIVST compared to provider-initiated testing and counseling was reported to increase HIV testing in a cluster-randomized trial in Malawi [36]. While several HIVST studies, including implementation science projects, have been conducted in Africa and other countries [23], our systematic review of HIV testing interventions literature in the Caribbean [37] revealed that only two studies have focused on HIVST in the Caribbean region [38,39]. Since the publication of this systematic review, results from a recent study in Puerto Rico revealed that the use of HIVST kits to screen sexual partners was acceptable and helped identify partners of positive HIV status among men who have sex with men (MSM) and transgender women, including sex workers, though some participants faced negative partner reactions when broaching the topic of HIVST [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 27.1% of testers cited the convenience of getting their results on the same day as a reason for testing 38. Another article reported that participants who expressed a test preference preferred oral fluids testing to fingerprick testing (65.8% vs 34.2%) 39…”
Section: Resultsmentioning
confidence: 99%